Naturally occurring anti-E red-cell antibodies in a 3-month old infant - Šimc, Mojca (Zdravniški vestnik, 2010)
Background: Before the transfusion of the red blood cells containing blood components is applied, pre-transfusion testing such as ABO, RhD and Kell bloodgrouping with a negative crossmatch is obligatory. This can be reduced toblood grouping only in infants less than 4 months of age, provided that the initial antibody screening test is negative. Only a few cases of antibody formation in such young infants have been described, the majority of them haveresulted from exposure to allogeneic transfusions. Case report: During thepre-transfusion testing, naturally occurring anti-E red blood cell antibodies were detected in a 3-month old male infant, who underwent surgery for atresia of the extra hepatic bile ducts followed by a bacterial infection.All immunohaematological tests were performed using the commercial gel column agglutination method, screening cells, RBC panel and enzyme-modified cells according to the manufacturerćs instructions. The passive transfer of anti-E antibodies with blood components and the transfer of the antibodies from the mother during pregnancy and also through lactation were excluded. Immunisation due to exposure to E antigen was ruled out by confirming the E-negativity of all the red blood cell units the infant had received and also by confirming the E-negativity of the mother. Conclusion: Although the naturally occurring anti-E red-cell antibodies are usually found in adults, we report here a case of a 3-month old infant, who had developed naturally occurring anti-E red cell antibodies.
Keywords: baby; Biliarna atrezija; Biliary Atresia; Blood Component Transfusion; Blood Grouping And Crossmatching; Dojenček; dojenčki; Eritrociti; eritrocitna protitelesa; Erythrocytes; Igg; Infant; Isoantibodies; Izoprotitelesa; Krvna sestavina, transfuzija; krvne skupine; Krvne skupine in navzkrižno določanje; protitelesa; Surgery; testiranje; transfuzija krvi